Improving the Ability of Microsoft Office to Develop Junior High School Student Learning - Pratama, Farhan; Dwi Nyoto, Rudi; Tursina; Muhardi, Hafiz; Desepta Isna Ulumi; Yus Sholva (Tanjungpura International Journal on Dynamics Economics, Social Sciences and Agribusiness, 2023)
Utilization of Information and Communication Technology (ICT) has touched almost all aspects of people's lives. The application of Information and Communication Technology is prioritized for application in education/learning processes. However, this utilization has not been evenly distributed at all levels of education. In the era of digitalization, the application of Information and Communication Technology in schools is to help them develop their skills later, where almost all lines of work use applications, especially Microsoft Office. Obstacles to the application of Information and Communication Technology include the lack of student skills in using computer applications, like Microsoft excel, Microsoft word and Microsoft power point. Therefore, it is necessary to provide Microsoft Office assistance and training to junior high school students so as to help them improve their skills in using Microsoft Office.